Russkaâ rečʹ v neoficialʹnom internet-obŝenii - Karpova, Tat’âna B. (Stylistyka, 2021)
Linguists in Russia estimate ambiguously the language of runet (Russian-speaking sector in internet). A generał trend to negligence of the Russian language, supplanting it by simplified English, adherence to slang and depressed vocabulary, destruction of ortho- graphic, punctuation and other norms is noticed.Especially distinctly it is manifested in unofficial internet intercourse, in such its genre forms as chat, forum, web-site, weblog, private correspondence by E-mail and using “I seek you” (ICQ and its analogs).In runet the traditions of Russian risorial culture are realized. Laughing and mocking, the internet “inhabitants” become bolder, feel morę confident, morę comfortable, inclu- ding in the language used as well. Computer-net slang in the runet fights actively with americanization by giving other meanings to terminology in a foreign language. It is an original way to make the internet accessible, pleasant, its own, Russian, it is a demonstra- tion of the emerged possibility to return the vivid naturę of non-edited spontaneous speech which was lost during domination of the bookish speech. Through cheerful camival humor of the runet “the emotional ecology of socium” is improved, and the language play is an “active tool of catharsis”.It is remarkably to notę that the Russian mentality in generał is characterized by a disli- ke to strict regulation, conventionalities, where actually any everyday culture-conditio- ned regulation of the behavior is meant. That is why the runet is sensitive to new, non-standard and deviant units of speech if they differ by sufficient expressiveness. And even epatage vocal forms acquire in the internet medium the function of accentuation of a human individuality, originality and thus realize the desire of a speaker deviating from norms of behavior to be noted, to attract attention.Therefore, the determinant of vocal self-realization of a personality in non-formal runet is playing improvisation style typical for today’s cultural context defined by many as time of postmodemism. We can also notę here another-maximum confiding, private style when there is “intercourse in virtual with masks down”. Such a zonę of elevated emo- tionality is, for example, weblogs. During functioning a Russian-speaking personality in runet, the typical features of Russian national character become apparent, such as particu- lar emotionality, anti-rationality, inclination to passivity and fatalism, love for moral .